Effect of the Side-Chain Length in Perfluorinated Sulfonic and Phosphoric Acid-Based Membranes on Nanophase Segregation and Transport: A Molecular Dynamics Simulation Approach - Lawler, Robin; Caliendo, Charles; Ju, Hyunchul; Kim, Jin Young; Lee, Seung Woo; Jang, Seung Soon (AMER CHEMICAL SOC, 2020)
The effect of side-chain length on the nanophase-segregated structure and transport in perfluorinated sulfonic acid (PFSA)-based and perfluorinated phosphoric acid (PFPA)-based membranes is investigated at 20 and 5 wt % water content conditions using a molecular dynamics simulation method. It is found using the pair correlation analysis that the longer side chain leads to more developed local water structures in the water phase at 20 wt % water content, observable in both membrane chemistries albeit more distinct in PFPA-based membranes. It is also confirmed from the structure factor analysis that large-scale nanophase segregation is enhanced with increasing side-chain length for PFPA membranes, whereas no significant change is observed at these scales for PFSA membranes. Next, it is revealed that the proton transport is increased by 0.004 S/cm in PFSA-based membranes with increasing side-chain length due to the enhanced vehicular and hopping mechanisms, whereas the proton transport in PFPA-based membranes is decreased by 0.002 S/cm despite improved nanophase segregation. As confirmed by the pair correlation function analysis, the diminished proton transport in PFPA-based membranes is attributed to the molecular association of phosphate groups with hydronium ions via hydrogen bond in the longer side-chain case, which is namely a hydronium-mediated bridge configuration. Such bridge configurations and correspondingly similar trends in proton transport are also observed at 5 wt % water content condition to a lesser extent. Our simulation study demonstrates that the proton transport is affected by the hydrogen-bonding network as well as by the nanophase segregation.